A mixed-method study on gender and intrahousehold differences in food consumption from Khatlon Province, Tajikistan - Pechtl, Sarah; Mardonova Tolibkhonovna, Mohru; Ergasheva, Tanzila; Lambrecht, Isabel B. (International Food Policy Research Institute, 2024)
Tajikistan faces food insecurity and multiple forms of malnutrition in its population, with women particularly at risk. Social norms related to gender and intrahousehold hierarchy are pervasive and are commonly upheld in household roles. Yet, how gender may impact dietary intake in Tajikistan remains to be studied. Understanding this mechanism is critical to develop adequate strategies for effective, equitable progress in mitigating malnutrition and food insecurity. mixed-methods study was conducted to assess the extent and identify the drivers of gender-based and intrahousehold differences in dietary intake in Khatlon Province, Tajikistan. Predictors of food intake and dietary diversity were statistically assessed using quantitative survey data from 1,704 individuals collected in winter- and springtime 2023. Qualitative data from 12 focus group discussions, 20 individual interviews, and 22 Photovoice interviews collected in winter- and springtime 2024 was analyzed using reflexive thematic analysis to further ascertain and understand these drivers. We find gender differences in dietary diversity, with women reporting lower dietary diversity than men, even when comparing men and women living in the same household. Among women, there are significant differences in dietary diversity based on their role in the household. Gendered social norms and intrahousehold power relations influence food acquisition, preparation, distribution, and consumption. Men, particularly household heads, and children tend to be prioritized over women in consuming food products that are deemed more nutritious (e.g., meat). Women adapt their food intake to meet the expectations and needs of other household members. This study highlights the importance of considering household dynamics and gender roles when creating programs and policies aiming to equitably address food and nutrition insecurity and malnutrition. The findings suggest that mitigating malnutrition in Tajikistan will necessitate gender equity-focused social behavior change interventions targeting women and men across different generations.